EARLY PHYSICAL REHABILITATION FOR CHILDREN WITH ERB’S PALSY: A SYSTEMATIC REVIEW - Dzulkifli, Nurul Hafizah; Abdul Rahman, Rozlin; Azizan, Noor Azliyana (International Journal of Allied Health Sciences, 2021)
Early physical therapy intervention has a significant impact on improving the impairments and disabilities of Erb’s Palsy patients. Proper early assessments and management by physical therapists can reduce physical complications and mental health problems, thus enhancing the child’s opportunities to return to their maximal activity daily living (ADL). This review aims to identify the early physical rehabilitation treatments for children with Erb’s Palsy. This objective is fulfilled by using the systematic review method following the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guideline. The search from Web of Sciences (WoS), PubMed, Science Direct, Scopus, PEDro and Google Scholar databases yielded 245 records. Twenty-nine full-text articles were assessed and six eligible articles were further reviewed. The study summarized that physical therapy treatments should be started as early as the condition being diagnosed. Treatment is found to be more effective when conventional physical therapy treatments are combined with advanced exercise consists of plyometric, modified constrained induced movement therapy (MCIMT) and virtual reality (VR). This review enables physical therapists in Malaysia to plan proper and suitable treatments for Erb’s palsy patients according to the injury’s level and severity.